An Analysis of Emerging Trends in Economic Diplomacy: A Comparison between Group of Seven (G7) and BRICS Alliance - Paudel, Damaru Ballabha (Journal of Foreign Affairs, 2023)
Economic diplomacy is the use of diplomatic apparatuses and strategies to promote a country’s economic interests abroad. This involves negotiating favorable trade agreements with other countries, attracting foreign investment, or facilitating international cooperation in areas such as technology transfer or development assistance, tourism promotion and use of economic intelligence to promote the economic wellbeing of a country. The conventional international economic order comprises of Breton-wood institutions, world trade organizations and global resource control of advanced economics such as G7 group. However, the emerging order involves the rise of new economic powers in the developing world such as BRICS group, AIIB and the rising economic power of their currency including proposed BRICS currency. In this article, I will attempt to analyze the traditional as well as emerging trends that shape the new economic world order.